A public health ethics framework for the older community: A South African perspective - Lategan, Laetus O.K.; van Zyl, Gert J.; Kruger, Willem H. (Koers (Potchefstroom, South Africa), 2024)
An ethical framework for dealing with geriatric communities is mostly absent in developing countries. This article presents an ethics framework for public health that can be used to address older persons' communities and their associated vulnerability. A mixed methods approach was used for the design of this framework. A principal component analysis was employed to summarise the information content. The rotated component matrix identified nine determinants from the survey outcome. A five-point Likert scale rated fifty statements relevant to care for older persons. The rating of the mentioned statements confirmed that social determinants influence older persons' health. Furthermore, such statements' ratings also highlighted the role of government and support systems in the care of older persons. The evident link between social determinants and ethics was noteworthy, as well as the fact that social determinants contribute towards ethical challenges. It was further confirmed that an ethical framework could contribute towards health and judgements concerning older communities. Opsomming ‘n Etiese raamwerk met die oog op die hantering van ouer gemeenskappe is meestal nie beskikbaar in ontwikkelende lande nie. Hierdie artikel bied ‘n etiek-raamwerk vir openbare gesondheid wat gebruik kan word om ouerpersone-gemeenskappe en hul gepaardgaande broosheid te hanteer. Vir die ontwerp van hierdie raamwerk is ’n gemengdemetode-benadering gebruik. ‘n Hoofkomponentanalise is aangewend om die inhoud van die inligting op te som. Die gedraaide komponentmatriks het nege faktore geïdentifiseer wat op die uitkoms van die opname/dataversameling gebaseer is. ‘n Vyfpunt-Likertskaal is gebruik om stellings wat op die sorg van ouer persone betrekking het te takseer. Die taksering van die genoemde stellings het bevestig dat sosiale faktore ’n invloed op die gesondheid van ouer persone uitoefen. Voorts het die taksering van die sodanige stellings ook die owerheid en ondersteuningstelsels se rol in ouer persone se versorging beklemtoon. Die voor die hand liggende skakel tussen sosiale faktore en etiek was opmerklik, asook die feit dat sosiale faktore tot etiese uitdagings bygedra het. Daar is verder bevestig dat ’n etiese raamwerk tot die gesondheid van ouer persone en hul versorging kan bydra.